Measuring cross-section data for prompt gammas emitted during proton-nucleus collisions - Ramanathan, Vijitha (Department of Physics, 2018)
In Radiation Oncology, proton therapy has become an increasingly popular treatment modality due to the superior dose distribution of the proton beam while sparing more surrounding normal healthy tissues and critical organs. This advantage can quickly turn into a disadvantage if there is any uncertainty in the delivery of the proton beam. To fully utilize the benefits of proton therapy, it is important to monitor the in-vivo dose deposition. Due to the fact that the treatment protons stop within the patient as they deliver the dose, secondary radiation is the potential method to obtain a dose verification measurement. The detection of secondary prompt gamma rays have been proposed as an in-situ method to determine the proton range since the location of the prompt gamma emission is strongly correlated with the proton depth dose profile. This correlation has been confirmed in both experimental measurements and in Monte Carlo simulations, but absolute prompt gamma productions have been unsuccessful, due to discrepancies the Monte Carlo prompt gamma production data particularly for the prominent elements found in tissue within the therapeutic range (50-200 MeV). The goal of this work was to evaluate the prompt gamma production for both carbon and oxygen at energies relevant for proton therapy. The first part of this study was to experimentally measure the interaction cross section for proton-nucleus collisions in both carbon and oxygen. In order to determine these cross-sections, measurements using thin targets of natural Carbon and Mylar over the energy range of 66-125 MeV were performed using the AFRODITE detector system at iThemba LABS in Cape Town, South Africa. Energy and efficiency calibrations of the detection system were performed using three standard gamma emitting sources (137Cs, 60Co, and 152Eu). The second part of this work was to model the AFRODITE detector system using the Geant4 Monte-Carlo radiation transport code in order to compare the simulated to the measured results and to evaluate the previously observed discrepancies for prompt gamma production in the Geant4 code.